A comprehensive evaluation of flexible FDM/FFF 3D printing filament as a potential material in medical application. (5th September 2020) - Haryńska, Agnieszka; Carayon, Iga; Kosmela, Paulina; Szeliski, Kamil; Łapiński, Marcin; Pokrywczyńska, Marta; Kucińska-Lipka, Justyna; Janik, Helena
Graphical abstract: Highlights: Medical grade flexible filament for FDM/FFF 3DP was studied. The influence of the FFF 3D printing process on the filament was investigated. FFF 3DP process did not affect the structure and properties of the filament. Incubation in SBF showed the bioactivity of the formed printouts. Filament has potential in FDM/FFF of medical devices or long-term bone implants. Abstract: The use of FDM/FFF in 3D printing for medical sciences is becoming common. This is due to the high availability and decent price of both 3D printers and filaments useful for FDM/FFF. Currently, researchers' attention is focused mainly on the study of medical filaments based on PLA, PCL or their modifications. This contributes to insufficient diversity of medical-grade filaments on the market. Moreover, due to the lack of specified standards for filaments testing, manufacturers often provide merely the characteristics of the raw materials, which were used for filaments fabrication. This lack of comprehensive data can be problematic when viewed as medical-grade material. As a consequence of this overview, we have performed a comprehensive evaluation of a flexible medical-grade filament for FDM/FFF 3DP - Bioflex® (Filoalfa). We have performed complex characterization through a variety of methods and techniques including spectroscopic analysis (FTIR, Raman), dynamic mechanical analysis (DMA), thermal properties (DSC, TGA), rheological characteristic (MFR). In the next step, printed Bioflex® samples were utilized to characterize the material behaviour after the 3D printing process. The mechanical analysis allowed to estimate how the material strength decreases after the printing process according to the values given in the technical data sheet. The contact angle measurements determined wettability of the Bioflex® printouts. Performed series of in vitro studies were carried out to assess its potential as as implantable structures. In conclusion, 3D printing process did not affect the printouts biocompatibility (ISO 10993:5). Accelerated degradation studies indicated elevated hydrolysis resistance of printed samples. In turn, performed incubation in simulated body fluid (SBF) solution, revealed carbonated hydroxyapatite (HAp) deposition on printouts surface indicating their bioactive properties. Thus, studied filament seems to be a suitable candidate for further development of FDM/FFF 3DP structures for advanced biological and medical application.